VALIDITAS KONSTRUK EFIKASI DIRI MATEMATIKA : Analisis Faktor Konfirmatori - Risnawati, Rini (Pascasarjana IAIN Kudus, 2013)
In this study, construct validity of mathematics self-efficacy was examined. Confirmatory factor analysis was conducted and followedwith testing the correlation among the factor of mathematicsself-efficacy. The subjects in this study amounted to 89 studentwho participated in the fulfilling scale. The results show that theconstruct of mathematics self-efficacy consists of four dimensionsi.e mastery experience, vicarious experience, verbal persuasionand emotional-physiological state.